2013
DOI: 10.4271/2013-01-1253
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Aerodynamics of an Oscillating Fastback Model

Abstract: This paper investigates the surface pressures found on the sides of a Davis model under steady state conditions and during yawed oscillations at a reduced frequency which would generally be assumed to give a quasi-static response. The surface pressures are used to investigate the flow field and integrated to infer aerodynamic loads. The results show hysteresis in the oscillating model's results, most strongly in the A-pillar flows. The changes to the flow field reduce strength of the flows around the rear pill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…The two Davis model configurations used in this paper have been previously used by [4] and [5] which allowing for direct comparisons of the simulation results presented in this paper with their previously published experimental works. Both works were conducted in the Loughborough University 1/4 scale wind tunnel.…”
Section: Experiments Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The two Davis model configurations used in this paper have been previously used by [4] and [5] which allowing for direct comparisons of the simulation results presented in this paper with their previously published experimental works. Both works were conducted in the Loughborough University 1/4 scale wind tunnel.…”
Section: Experiments Approachmentioning
confidence: 99%
“…Most common turbulence models including k-ε standard, k-ε realizable, k-ω standard and k-ω SST are tested in this study. Simulation generated centerline pressure distribution over the top surface of the round-edged model had been compared with data collected using Electronic Pressure Scanners as in reference [4]. Results from k-ε standard and k-ε realizable turbulence model correlated poorly against the experimental results compare to the two kω models and it was observed that k-ω SST model provided the closest agreement in pressure coefficient values against the experimental test data as in Fig.…”
Section: Cfd Simulation Approachmentioning
confidence: 99%